HUBUNGAN MOTIVASI PEMELIHARAAN KESEHATAN GIGI DAN MULUT TERHADAP KUALITAS HIDUP DALAM KESEHATAN GIGI DAN MULUT PADA MAHASISWA JURUSAN KESEHATAN GIGI DAN MAHASISWA MANAJEMEN SUMBERDAYA MANUSIA APARATUR (Poltekkes Kemenkes Bandung, 2022)
ABSTRACT Dental and Oral health problems can be caused by a persons lack of motivastion for the quality of his life. Health problems found ther are 51,9% of adolescents aged 15-24 years suffering from dental and oral health behavio is known to be lacking and low. This study aims to analyse the relationship between motivastion and quality related of life (Oral health Related Quality of Life- OHQRoL) student of Department of dental health and student of Apparatus Human Resources Managemant. This type of research is analytic with a cross-sectional design. The data were analysed using the Fisher Exact Test. The results showed that student who had strong motivastion and good quality of live in JKG students obtained 26 respondent (60.4%) with p = 0.656 and MSDMA students obtained 11 respondent (25.6%) with p = 0.735 showed that there was no statistically significant relationship between motivation and quality of life. The conclusion of this study is that there is no significant relationship between motivastion and OHQRoL, for students of Department of dental health and student of Apparatus Human Resources Managemant.